Profitability, Liquidity, and Asset Structure in Debt Policy Decisions: A Literature Review - Nelly Ervina; Riny Riny; Ernest Grace; Julyanthry Julyanthry; Raya Panjaitan (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
In today’s competitive business environment, corporate debt policy significantly influences financial stability and growth, shaped by firm-specific factors like profitability, liquidity, and asset structure. This study aims to examine how these factors affect debt policy decisions through a systematic literature review. The review analyzes 42 peer-reviewed articles published between 2020 and 2025, sourced from databases such as Scopus, Web of Science, ScienceDirect, and Emerald Insight, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework. Findings reveal that profitability generally reduces debt reliance, as firms favor internal financing, aligning with the Pecking Order Theory. Liquidity also tends to decrease borrowing, though it can enhance creditworthiness in capital-intensive sectors. Conversely, asset structure, particularly tangible assets, consistently correlates positively with debt, supporting the Trade-Off Theory by providing collateral. Contextual factors like industry, firm size, and economic conditions influence these relationships. The study concludes that while established theories explain debt policy, contextual nuances necessitate tailored financial strategies. This review contributes to corporate finance by offering a comprehensive, theory-driven synthesis, highlighting practical implications for managers and identifying future research avenues to address sector-specific and regional variations.